Efficacy of B cell Depletion Therapy on Joint Flare is Associated with Increased Lymphatic Flow - Li, Jie (2013)
OBJECTIVE: B cell depletion therapy (BCDT) ameliorates rheumatoid arthritis by mechanisms that are incompletely understood. Arthritic flare in tumor necrosis factor transgenic (TNF-Tg) mice is associated with efferent lymph node (LN) “collapse,” triggered by B cell translocation into lymphatic spaces and decreased lymphatic drainage. We examined whether BCDT efficacy is associated with restoration of lymphatic drainage due to removal of obstructing nodal B cells. METHODS: We developed contrast-enhancement (CE) MRI imaging, near-infrared indocyanine green (NIR-ICG) imaging, and intravital immunofluorescent imaging to longitudinally assess synovitis, lymphatic flow, and cell migration in lymphatic vessels in TNF-Tg mice. We tested to see if BCDT efficacy is associated with restoration of lymphatic draining and cell egress from arthritic joints. RESULTS: Unlike active lymphatics to normal and pre-arthritic knees, afferent lymphatic vessels to collapsed LNs in inflamed knees do not pulse. Intravital immunofluorescent imaging demonstrated that CD11b(+) monocytes/macrophages in lymphatic vessels afferent to expanding LN travel at high velocity (186 ± 37 micrometer/sec), while these cells are stationary in lymphatic vessels afferent to collapsed PLN. BCDT of flaring TNF-Tg mice significantly decreased knee synovial volume by 50% from the baseline level, and significantly increased lymphatic clearance versus placebo (p<0.05). This increased lymphatic drainage restored macrophages egress from inflamed joints without recovery of the lymphatic pulse. CONCLUSION: These results support a novel mechanism in which BCDT of flaring joints lessens inflammation by increasing lymphatic drainage and subsequent migration of cells and cytokines from the synovial space.